Merging transport network companies and taxis in Curitiba's BRT system - Rafael Milani Medeiros; Fábio Duarte; Iva Bojic; Yang Xu; Paolo Santi; Carlo Ratti (Public Transport, 2023)
The Brazilian city of Curitiba became known around the world for pioneering bus rapid transit (BRT) in the 1970s. Five decades later, public transport ridership is declining on the city's bus-based system. One-person car trips and car ownership are soaring, and services provided by transport network companies rapidly proliferate and then disappear as congestion worsens and expands across the road network. This was the macro-scale scenario for mobility and modal trends in Curitiba until COVID-19 brought things to a screeching halt in 2020. The widespread use of information and communication technologies has allowed taxi and car ride-hailing transport network schemes to emerge while blurring the lines between public and private and individual and collective transport, locally as well as globally. In 2016, transport network company systems, apps, private cars, services, drivers and passengers disrupted Curitiba's longstanding and well-regulated taxi system and market for licenses. In 2023, hailing a cab or a shared ride feels and costs the same for passengers (now customers). This study investigates whether these actors and technologies compete with or complement each other in this city, locating and quantifying the benefits for passengers of merging taxi and car ridesharing with the BRT system as first- and last-mile transport to and from BRT corridors. We developed mobile information and communication technologies and acquired, processed, and analyzed millions of data points for passenger location on BRT, ordinary bus, and taxi trips at the city scale. The shareability index for Curitiba's taxi or car rides was calculated, demonstrating that 60% of all taxi trips have the potential to serve as first- and last-mile transport solution to and from~the BRT terminals, stations, and corridors and that nearly 40% of taxi trips both originate and end near~(<~500~m) this BRT system infrastructure. By envisioning how transport network companies could merge into the built environment thanks to urban transport digitization, we have developed a model for integrating public transport with the analytic framework of transport network companies that could be deployed in other cities with similar challenges related to public transport, sociotechnical arrangements, system complexity, policymaking, and planning.
Keywords: 380; Public transport integration; Bus rapid transit; Taxi; Car ridesharing; Ride-hailing; Trip chaining